A constellation of science-based data driven products to improve financing of Sustainable Agri-Food Systems - Burra, Dharani Dhar; Vyas, Shalika; Molina, Luis; Estrada-Carmona, Natalia; Francesconi, Wendy; Ramírez Villegas, Julián Armando; Newman, Richard; Grosjean, Godefroy (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Investing in agri-food systems in developing countries is often considered risky, specifically for private investors, and impacts are difficult to quantify leading to an insufficient allocation of capital to the sector. This is caused due to Information asymmetries and poor primary data between financial institutions and potential borrowers in rural financial markets. This results in inadequate risk, return, impact assessment models and high transaction costs for capital deployment.To overcome these challenges, we have developed the "OneSF Analyzer", a "constellation" of data-products designed to "de-risk" investments, through multidimensional assessments and monitoring of agri-food systems (productivity, environment, gender etc.), along with financial health assessments of the investee. in this report, we present the science, data, analytics, and the design components of agro-climatic hazards and their impacts on crop productivity (Phase 1) of "OneSF Analyzer". We also present phase wise planned improvements to the OneSF Analyzer both with regards to scalability/computation, as well as expanding insights to support pre-investment decisions by financial institutions.